Evaluating intrinsic and non-intrinsic cancer risk factors - Song Wu (Nature Portfolio, 2018)
Understanding the contributions of extrinsic and intrinsic factors on cancer risk is fundamental in determining the intervention and prevention strategies to tackle cancer. Here the authors provide a review of the different factors impacting cancer risk and discuss the limitations of different approaches in evaluating the relative contributions of these factors.